PROSPECTS FOR THE DEVELOPMENT OF CRYPTOCURRENCIES IN THE NEAR FUTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the problems of a new type of electronic money - cryptocurrencies. It is shown that today there is no common understanding of cryptocurrency in the world in some sources, cryptocurrency is defined as the currency of the future, in others - as something unpromising. In accordance with this, the existing formulations of cryptocurrencies were studied and the opinions of experts in the field of electronic money were considered.